PENGARUH PERLINDUNGAN EKONOMI TERHADAP KESEJAHTERAAN TENAGA KERJA OUTSOURCING PADA PT PLN AREA LHOKSEUMAWE - Zusma Widawaty; Kheriah Kheriah; Elvina Elvina (Ekonis: Jurnal Ekonomi dan Bisnis, 2018)
Abstract:  Economic protection is a legal protection given to the workforce to obtain economic rights such as getting a salary payment plus other incentives to be able to meet the needs of his life. Provision of salaries and other incentives by employers should be based on minimum provincial minimum wage (UMP) standards. Outsourced workforce consists of non-permanent labor and labor over time. This study aims to determine the effect of economic protection after the Decision of the Constitutional Court Number 27 / PUU-IX / 2011 to the welfare of outsourcing workers. Sampling is done by purposive sampling. Data collection techniques are conducted through primary data by distributing questionnaires to outsourced labor, whereas secondary data are derived from books or sources of scientific data and legislation in the field of employment related to the problems in this study. This study uses two hypotheses. To test the hypothesis is done by using the method of validity and reliability testing. The data analysis technique used is multiple linear regression analysis. The result of the research shows that economic protection, both simultaneously and partially, has an effect on the increase of labor welfare outsourcing at PT. PLN (Persero) Area Lhokseumawe, this can be seen from the value of Fhitung for s27.155, while Ftabel at the level of significance µ = 5% is equal to 2,766.Keywords: Protection of employment law, economic protection, welfare and outsourced labor.